Loss of cAMP-specific phosphodiesterase rescues spore development in G protein mutant in Dictyostelium - Schwebs, David J. (2014)
Cyclic AMP (cAMP) is an important intracellular signaling molecule for many G protein-mediated signaling pathways but the specificity of cAMP signaling in cells with multiple signaling pathways is not well-understood. In Dictyostelium, at least two different G protein signaling pathways, mediated by the Gα2 and Gα4 subunits, are involved with cAMP accumulation, spore production, and chemotaxis and the stimulation of these pathways results in the activation of ERK2, a mitogen-activated protein kinase that can down regulate the cAMP-specific phosphodiesterase RegA. The regA gene was disrupted in gα2(−) and gα4(−) cells to determine if the absence of this phosphodiesterase rescues the development of these G protein mutants as it does for erk2(−) mutants. The regA(−) mutation had no major effects on developmental morphology but enriched the distribution of the Gα mutant cells to the prespore/prestalk border in chimeric aggregates. The loss of RegA function had no effect on Gα4-mediated folate chemotaxis. However, the regA gene disruption in gα4(−) cells, but not in gα2(−) cells, resulted in a substantial rescue and acceleration of spore production. This rescue in sporulation required cell autonomous signaling because the precocious sporulation could not be induced through intercellular signaling in chimeric aggregates. However, intercellular signals from regA(−) strains increased the expression of the prestalk gene ecmB and accelerated the vacuolization of stalk cells. Intercellular signaling from gα4(−)regA(−) strain did not induce ecmA gene expression indicating cell-type specificity in the promotion of prestalk cell development. regA gene disruption in a Gα4(HC) (Gα4 overexpression) strain did not result in precocious sporulation or stalk cell development indicating that elevated Gα4 subunit expression can mask regA(−) associated phenotypes even when provided with wild-type intercellular signaling. These finding indicate that the Gα2 and Gα4-mediated pathways provide different contributions to the development of spores and stalk cells and that the absence of RegA function can bypass some but not all defects in G protein regulated spore development.